Hypoxic culture conditions as a solution for mesenchymal stem cell based regenerative therapy - Haque, Nazmul; Rahman, Mohammad Tariqur; Abu Kasim, Noor Hayaty; Alabsi, Aied Mohammed (Hindawi Publishing Corporation, 2013)
Cell-based regenerative therapies, based on in vitro propagation of stem cells, offer tremendous hope to many individuals suffering from degenerative diseases that were previously deemed untreatable. Due to the self-renewal capacity, multilineage potential, and immunosuppressive property, mesenchymal stem cells (MSCs) are considered as an attractive source of stem cells for regenerative therapies. However, poor growth kinetics, early senescence, and genetic instability during in vitro expansion and poor engraftment after transplantation are considered to be among the major disadvantages of MSC-based regenerative therapies. A number of complex inter- and intracellular interactive signaling systems control growth, multiplication, and differentiation of MSCs in their niche. Common laboratory conditions for stem cell culture involve ambient O2 concentration (20%) in contrast to their niche where they usually reside in 2–9% O2. Notably, O2 plays an important role in maintaining stem cell fate in terms of proliferation and differentiation, by regulating hypoxia-inducible factor-1 (HIF-1) mediated expression of different genes. This paper aims to describe and compare the role of normoxia (20% O2) and hypoxia (2–9% O2) on the biology of MSCs. Finally it is concluded that a hypoxic environment can greatly improve growth kinetics, genetic stability, and expression of chemokine receptors during in vitro expansion and eventually can increase efficiency of MSC-based regenerative therapies. ,1,2 ,3 ,1,2 and